2020
DOI: 10.1101/2020.07.30.228163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A persistent giant algal virus, with a unique morphology, encodes an unprecedented number of genes involved in energy metabolism

Abstract: Viruses on Earth are tremendously diverse in terms of morphology, functionality, and genomic composition. Over the last decade, the conceptual gap separating viruses and cellular life has tightened because of the detection of metabolic genes in viral genomes that express complex virus phenotypes upon infection. Here, we describe the 1.4 MB linear genome of Prymnesium kappa Virus RF01 (PkV RF01), a large alga-infecting virus of the Mimiviridae family with a unique morphology, an atypical infection profile, and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 121 publications
(162 reference statements)
0
9
0
Order By: Relevance
“…It was further proposed that these viruses should form part of an extended Mimiviridae [ 11 , 13 , 42 , 74 , 75 ] or even the subfamily Mesomimivirinae within Mimiviridae [ 42 , 43 , 76 ] ( Figure 1 ). Mesomimivirinae is certainly expanding as most newly reported alga-infecting viruses join this clade instead of Phycodnaviridae , such as the viruses from Florenciella , Rhizochromulina , a chlorarachniophyte, and Prymnesium kappa [ 51 , 52 , 77 ] (not shown in Figure 1 ). These, plus the viruses of heterotrophic flagellates Cafeteria , Bodo , and Bicosta , all transform Mimiviridae into a more non-amoebal virus family.…”
Section: Giant Viruses Infect Every Major Eukaryotic Lineagementioning
confidence: 99%
See 2 more Smart Citations
“…It was further proposed that these viruses should form part of an extended Mimiviridae [ 11 , 13 , 42 , 74 , 75 ] or even the subfamily Mesomimivirinae within Mimiviridae [ 42 , 43 , 76 ] ( Figure 1 ). Mesomimivirinae is certainly expanding as most newly reported alga-infecting viruses join this clade instead of Phycodnaviridae , such as the viruses from Florenciella , Rhizochromulina , a chlorarachniophyte, and Prymnesium kappa [ 51 , 52 , 77 ] (not shown in Figure 1 ). These, plus the viruses of heterotrophic flagellates Cafeteria , Bodo , and Bicosta , all transform Mimiviridae into a more non-amoebal virus family.…”
Section: Giant Viruses Infect Every Major Eukaryotic Lineagementioning
confidence: 99%
“…Giant viruses exert control over different levels of genetic information in a cell. In addition to their own DNA polymerase and ligase for genome replication, some giant viruses encode DNA glycosylase involved in base excision repair pathways that could potentially remove damages to their large genomes [ 77 , 99 ]. Most NCLDVs also encode DNA-dependent RNA polymerase (DDRP) subunits ( Table 1 ) with architectural modifications that confer them higher speed and processivity than the cellular homologs [ 54 ].…”
Section: Functional Potential Of Virus-encoded Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower recurrence and persistence of Mimiviridae ASVs than eukaryote ASVs may be due to the existence of multiple Mimiviridae that can infect the same host species. A recent study suggested that Mimiviridae that infect K -strategist eukaryotes have long infection and latent periods to maximize the chance of vertical transmission, since the chances of horizontal transmissions are low due to the low host density (44). Viruses of K -strategist eukaryotes are more likely to exist inside the host cell (i.e., a long latent period), while viruses of r -strategist eukaryotes are more likely to be found outside their host (i.e., they show higher virulence and tend to produce virions more quickly) (44).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that Mimiviridae that infect K -strategist eukaryotes have long infection and latent periods to maximize the chance of vertical transmission, since the chances of horizontal transmissions are low due to the low host density (44). Viruses of K -strategist eukaryotes are more likely to exist inside the host cell (i.e., a long latent period), while viruses of r -strategist eukaryotes are more likely to be found outside their host (i.e., they show higher virulence and tend to produce virions more quickly) (44). The size fraction we used for the detection of viral sequences (0.2–0.8 μm) may be enriched in free virions, which might have led to the preferential detection of r -strategist Mimiviridae .…”
Section: Discussionmentioning
confidence: 99%